Change in the Core Conflictual Relationship Themes of anxious patients receiving online psychodynamic psychotherapy (Research, Society and Development, 2022)
The core conflictual relationship is a pattern by which the individual establishes their interpersonal relationships, and its origin derives from regressive core conflicts. It is not known whether online psychodynamic psychotherapies produce changes at the intrapsychic level and are capable of altering the dysfunctional pattern of patients. Therefore, the aim was to explore possible changes in the conflictual relationship pattern expressed in the final sessions in relation to the initials sessions of patients receiving online psychodynamic psychotherapy. This was a naturalistic and longitudinal investigation through a systematic case study. Six patients with symptoms of anxiety participated. The Core Conflictual Relationship Theme instrument was used to extract the central relational pattern of the patients from the psychotherapy narratives. The data were collected through the transcription of the audio and video recordings of the sessions that comprised the treatments. A total of 120 relationship episodes, from 25 sessions, were descriptively and comparatively analyzed. The results showed changes in desires, and responses of others and self that indicate intrapsychic changes due to the distance treatment. Clinical evidence is also presented that can guide psychotherapists in the process of psychotherapeutic change. Limitations and suggestions for future research are discussed.